Analisis Peran Kurikulum Merdeka dalam Meningkatkan Keterampilan Siswa Tata Kecantikan SMKN 6 Semarang melalui Observasi - Mia Hafizah Tumangger; Ade Novi Nurul Ihsani; Avis Nur Azimah; Keisha Najiha Aqila; Ratu Jauza Rinaldi; Najwa Diyan Evana Putri; Mellodya Nindyatera (Journal on Education, 2025)
This study aims to analyze the role of the Independent Curriculum in the Skin and Hair Beauty program in improving student skills at SMK State 6 Semarang. The method used is descriptive observation, with data collection through direct observation of practical learning activities, interviews with teachers, and documentation of results. The results show that the implementation of the Independent Curriculum provides space for students to be more independent and creative in learning beauty practices. Through projects and competency-based learning, students are able to develop technical skills such as facial skin care, hair styling, and the optimal use of modern beauty tools. In addition, teachers act as facilitators who encourage students to innovate and take responsibility for their work. In conclusion, the implementation of the Independent Curriculum contributes positively to improving students' skills, independence, and learning motivation in the field of skin and hair beauty.